2008
DOI: 10.1177/0003319708321102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atorvastatin on Vascular Intimal Hyperplasia: An Experimental Rodent Model

Abstract: Atorvastatin suppresses intimal hyerplasia and aids in intimal regeneration by lowering blood lipids and intimal smooth muscle cell accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
1
15
0
2
Order By: Relevance
“…Since both ROS and systemic inflammation are responsible for increased ADMA levels, and statins are recognized as anti-inflammatory and antioxidant agents 41 , the hypothesis was that statin therapy might decrease ADMA levels. Indeed, several smaller studies have shown that statin therapy reduces ADMA levels 25,42 , however other studies with high dose statins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since both ROS and systemic inflammation are responsible for increased ADMA levels, and statins are recognized as anti-inflammatory and antioxidant agents 41 , the hypothesis was that statin therapy might decrease ADMA levels. Indeed, several smaller studies have shown that statin therapy reduces ADMA levels 25,42 , however other studies with high dose statins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that statins exert significant BP-lowering effects, particularly on systolic BP [161,[163][164][165]. Furthermore, animal models revealed that statins decrease the severity of lipid-induced glomerular damage and thus preserve renal function [110,[166][167][168]. In humans, statins may have a favorable impact on the slowing of CKD progression, since it was proved that they significantly decrease proteinuria [169,170].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Controlled and randomized clinical trials do not definitively support the clinical efficacy of statins in CKD and HD patients. Laboratory data also provide evidence for the biochemical and anti-inflammatory benefit of statins that should not be ignored despite the lack of comprehensive clinical evidence [85][86][87]. Nevertheless, the routine use of statins in this population remains the decision of individual physicians in discussion with their patients.…”
Section: Expert Opinionmentioning
confidence: 99%